The mitred Avalokitesvara from Palembang its significance on the origin and development of Srivijayan Art. - Nik Hassan Shuhaimi Nik Abdul Rahman. (Universiti Kebangsaan Malaysia, 1978)
The problems of "Srivijayan Art", the capital of Srivijaya and the relationship between Palembang and other parts of Srivijayan Empire from 7th to the 14th century A. D. are still being discussed. This essay is an attempt to bring forward a new evidence in helping to solve those problems. The study of the Avalokitesvara image discovered in Palembang, on the basis of the headdress, dhoti, body-shape, iconography and associated finds, shows that the image was made by a local artist in the 7th century A.D. Its headdress was the proto-type of the later Avalokitesvara images made in the Srivijayan Empire.